Universal human rights in theory and practice - Donnelly, Jack. (Ithaca : Cornell University Press, 2013)
In the third edition of his classic work, revised extensively and updated to include recent developments on the international scene, international studies professor Jack Donnelly explains and defends a richly interdisciplinary account of human rights as universal rights. He shows that any conception of human rights--and the idea of human rights itself--is historically specific and contingent. Since publication of the first edition in 1989, this book has justified Donnelly's claim that "conceptual clarity, the fruit of sound theory, can facilitate action. At the very least it can help to unmask the arguments of dictators and their allies."--Adapted from back cover.
Part I: Toward a theory of human rights. The concept of human rights ; The Universal Declaration model ; Economic rights and group rights ; Equal concern and respect -- Part II: The universality and relativity of human rights. A brief history of human rights ; The relative universality of human rights ; Universality in a world of peculiarities -- Part III: Human rights and human dignity. Dignity : particularistic and universalistic conceptions in the West ; Humanity, dignity, and politics in Confucian China ; Humans and society in Hindu South Asia -- Part IV: Human rights and international action. International human rights regimes ; Human rights and foreign policy -- Part V: Contemporary issues. Human rights, democracy, and development ; The West and economic and social rights ; Humanitarian intervention against genocide ; Nondiscrimination for all : the case of sexual minorities.
Includes bibliographical references and index.
Keywords: Civil rights; Human rights; Cultural relativism; Civil rights; Cultural relativism; Human rights; Politics and Government